Pengaruh keganasan dalam media terhadap tingkah laku agresif remaja - Yaacob, Zaleha (2010)
The purpose of this research was to study violence in media and its effects on aggressive behavior of students. Respondents were students from three secondary schools in Permas Jaya Zone, Pasir Gudang, Johor. Participants for this study were 190 respondents comprising of 81 boys and 109 girls. Data were collected from the following questionnaires namely The Attractive Media and The Effect on Audience Questionnaire (Heinichi, Molenda, Russel and Ely), The Effect of Violent on Aggression (Bush and Perry), The General Aggression Model (Anderson and Dill, 2002) and Television Violence and The Adolescent (William, 1978). Test re-test method were used to determine their reliability. The Media and The Effect on Audience Questionnaire has a reliability of 0.833, where as the reliability indexes for The Effect of Violent on Aggression is 0.831, The General Aggression Model is 0.830 and Television Violence and The Adolescent are 0.828 and respectively. Descriptive statistics used to analyze the data were mean, percentage, frequency and t- test. The finding showed that aggressive students like to watch informative programs. There were no significant differences in the choice of aggressive boys and girls in two types of media programs namely a live telecast of event, and slow motion action, fast and recorded events. However there were significant differences in the choice of aggressive boys and girls in two types of media programs namely realism and information. Violent in media did not cause aggressive students to be violent in physical, verbal. emotional and sexual behavior except in the form of hostilities. Aggressive students liked to watch violent stories in the media and the most popular stories watched were about wars and action stories and the frequency of watching the media was about two to three hours daily. The level of violent behaviors as a result of watching violent media was low. The study has important implication in the role of media and the need to reevaluate the telecast of violent programs in order to minimize violence elements that can cause students to be aggressive.